2019
DOI: 10.1097/pgp.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 Expression in Common Gynecologic Carcinomas: A Potential Pitfall

Abstract: GATA binding protein 3 (GATA3) immunohistochemistry is primarily used as a marker of breast and urothelial differentiation, particularly in metastatic settings. In the gynecologic tract it also serves a robust marker for mesonephric and trophoblastic tumors. However, expression has also been described in more common malignancies of gynecologic tract including ovarian, endometrial, and cervical carcinomas. Data on the distribution of GATA3 expression in gynecologic malignancies is somewhat limited, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…GATA-3 was originally identified as an organspecific biomarker for breast and urothelial differentiation, but with commonly less frequent expression, it has been identified in several other carcinomas including endometrial carcinoma. [2][3][4][5][6][7][8][9][10] Thus, its expression could be a potential pitfall when making a pathologic diagnosis and should be interpreted in an appropriate clinicopathological context. In our case, GATA-3 nuclear expression was weakly identified in <50% of the cells in a metastatic breast lesion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…GATA-3 was originally identified as an organspecific biomarker for breast and urothelial differentiation, but with commonly less frequent expression, it has been identified in several other carcinomas including endometrial carcinoma. [2][3][4][5][6][7][8][9][10] Thus, its expression could be a potential pitfall when making a pathologic diagnosis and should be interpreted in an appropriate clinicopathological context. In our case, GATA-3 nuclear expression was weakly identified in <50% of the cells in a metastatic breast lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature, GATA-3 expression in endometrial carcinomas ranged in frequency from 0% to 13%. 7,10 Studies quantifying GATA-3 expression in endometrial lesions are summarized in Table 1. [3][4][5][6][7][8][9][10] GATA-3 expression in endometrial lesions was reported as being of weak to moderate intensity in the majority of cases in all studies, with a single exception.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations